Impact of Work-Life Balance on Job Satisfaction and Its Influence on Consumer Preference towards Organic Food Products in Chennai City - Devi T, Chitra; Chitra, C. (Journal of Neonatal Surgery, 2025)
In today’s fast-paced urban lifestyle, maintaining a healthy work-life balance has become increasingly important, not only for employee well-being and job satisfaction but also for influencing personal choices, including dietary habits and the interrelationship between work-life balance, job satisfaction, and consumer preference for organic food products among working individuals in Chennai City. As awareness regarding health and sustainable living grows, there is a noticeable shift in consumer behaviour, particularly toward organic food consumption. The study hypothesizes that individuals with a better work-life balance experience higher levels of job satisfaction and are more inclined toward health-conscious consumption, reflected in their preference for organic products. The study involving both quantitative and qualitative analyses a structured questionnaire was distributed to 600 respondents employed in various sectors within Chennai, capturing data on their work-life balance experiences, job satisfaction levels, and purchasing behaviour related to organic food. Descriptive statistics, correlation analysis, and regression models were applied to understand the relationships among the variables. The findings reveal a significant positive correlation between work-life balance and job satisfaction, and a subsequent influence on organic food preferences. Respondents reporting higher work-life balance were more likely to be aware of the benefits of organic food and willing to invest in healthier food options. This suggests that professional satisfaction can indirectly promote healthier lifestyle choices also factors such as income, education level, and family responsibilities as moderating variables.